Workload, Tenure Auditor and Industrial Specialization Auditors on Audit Quality with Audit Committee as Moderating - T. H. Manurung, Daniel; Ligar Hardika, Andhika; Mulyati, Yati; Haizam Mohd Saudi, Mohd (International Journal of Engineering and Technology, 2018)
This study aims to obtain empirical evidence on audit quality on workload, auditor tenure and auditor industry specialization with the audit committee as a moderating variable. The study population was conducted on non-financial companies listed on the Indonesia Stock Exchange, a total sample of 10 companies research using purposive sampling. The research method uses moderating variables. The results of this study indicate that the workload affects audit quality while audit tenure and auditor industry specialization do not affect audit quality. This study found evidence that the interaction between workload and audit committee affects audit quality while the interaction of audit tenure and industry specialization does not affect audit quality.Â Â Â